Work-Life Balance on Performance of Career Women: Mediated by Family Support - Lina Mariana; Ceskakusumadewi Baharuddin; Panus Panus (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effect of work-life balance on the performance of career women and assess the role of family support as a mediating variable. This study seeks to provide empirical insight into how family and life role management affect the professional performance of women working in a police environment. Research Method: This study employs a quantitative approach, with primary data collected via questionnaires. The research sample comprised 25 female police officers and civil servants, selected using a total sampling technique. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and mediating effects of family support. Results and Discussion: The study indicates that work-life balance has a positive and significant effect on the performance of career women. In addition, family support has been proven to mediate this relationship, so that work-life balance supported by the family environment can strengthen the performance of female police officers in carrying out their official duties. Implications: This study contributes to the development of human resource management policies in police institutions, particularly regarding programs that support members' welfare and strengthen families' roles in supporting the performance of female personnel.